Effect of surface texturing on tribological performance of sliding guideway under boundary lubrication. (November 2019) - Yue, Hongzhi; Deng, Jianxin; Ge, Dongliang; Li, Xuemu; Zhang, Yun
Graphical abstract: Highlights: Reduction of friction force was found for textured guideways. Only-one-side textures were found to be more effective in preventing stick-slip motion. Parallel texture grooves on contacting surfaces were found to cause higher friction resistance and severe stick-slip motion. The occlusal contact of texture edge was found detrimental for the friction of both-side-textured surfaces. Abstract: The friction between textured surfaces was investigated by reciprocating sliding tests under similar operating conditions of sliding guideways. Micro-grooves parallel, perpendicular and 45° to sliding orientation were fabricated on the contacting surfaces of upper and/or lower guideways, and their tribological performance was evaluated with non-textured guideways as control group. The reduction of friction coefficient was observed for all the textured guideways, except for those with textures parallel to the sliding orientation. Lowest friction coefficient was achieved for both-side-textured guideways, while only-one-side textures were more effective in preventing stick-slip motion. The occlusal contact was found to be the main hindrance for improving tribological behavior by both-side texturing.